The influence of education on rural population employment: Regional disparities - Corina-Georgeta Dinculescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
A higher level and continuous education throughout entire life (necessary for adapting to the changes in the labor market) and a better health offer greater chances of sustained economic and social development. Also, a higher education level contributes to decrease the disparities between economic regions of development, due to the influence it has on employment population, in a particular area. The analysis may reveal regional employment disparities, sometimes severe, between development regions, representing a hindrance to economic development of the country, as a whole. The 8 development regions of Romania have certain particularities (features) in terms of employment, which makes some characteristics (demographic, educational etc.) to impart significant influence on employment.This paper aims to highlight the features of the rural area, in terms of population participation in economic activity, and disparities between the development regions, in terms of employment of rural population, respectively the influence that the level of education has on employment, and how it is reflected in the employment rates of rural population (by age groups), but also ranking of the development regions from this point of view.
Keywords: J21; J24; I25; O15; 330; labour force; employment; regional disparities; level of education; rural area